The effect of work stress on blood pressure and fatigue among Universitas Gadjah Mada field operational workers (PK4L) - Dwianri, Daniar Ajeng; Prabandari, Yayi Suryo (BKM Public Health and Community Medicine, 2022)
Purpose: This study aimed to know the effect of work stress on blood pressure and work fatigue in the field operation workers of PK4L UGM. Methods: This study was a quantitative study with a cross-sectional research design and equipped with a semi-structured interview. The sample size in this study was 163 respondents chosen using purposive sampling. Work stress is the independent variable measured using the HSE management standards indicator tool questionnaire. The dependent variables, blood pressure, were obtained from secondary data from health examination by PK4L UGM, and work fatigue (WF) was measured using the KAUPK2 questionnaire. The data were analyzed using bivariate analysis with Kendall's tau correlation test. Results: Out of 163 respondents, as many as 49.7% had a high WS, 24.5% had a high BP, and 31.3% had a severe WF. The causes of work stress were conflicts with a driver, increased workload, hot temperatures, work that requires high concentration, colleagues who are less able to work together, and monotonous work. The causes of work fatigue were increased workload, tedious work, sitting or standing for a long time, and mental exhaustion. Bivariate analysis showed that there was no effect of WS towards BP (p=0.752; τ= -0.025), and there was an effect of WS towards WF (p=0.010; τ=0.190). Conclusion: Work stress did not affect blood pressure, but it did impact work fatigue in the field operation workers of PK4L UGM. Further research is required to understand the other factors affecting workers' blood pressure and work fatigue.